Mitochondrial DNA Introgression in the European Abalone Haliotis tuberculata tuberculata: Evidence for Experimental mtDNA Paternal Inheritance and a Natural Hybrid Sequence - Van Wormhoudt, Alain; Roussel, Valérie; Courtois, Gercende; Huchette, Sylvain (Marine Biotechnology, 2011)
Two subspecies of the European abalone have been morphologically recognized: Haliotis tuberculata tuberculata, present in the North Atlantic, and Haliotis tuberculata coccinea, present in the Canary Islands. Among the different nuclear markers used to differentiate these two subspecies, the sperm lysin gene was the most reliable, leading to a 2.2% divergence. Concerning the subunit I of the mitochondrial cytochrome oxydase gene (COI), we observed a difference of 3.3% between the two subspecies. In the North Atlantic, an introgression of mitochondrial DNA from H. tuberculata coccinea to H. tuberculata tuberculata was evident in around 30% of individuals. Due to this difference, we were able to experimentally detect the transfer of paternal mitochondrial DNA (mtDNA) by specific quantitative polymerase chain reaction measurements. The presence of the two mtDNAsignatures was also detected in 20% of individuals tested in the field. Moreover, one mt DNA hybrid sequence was identified. The sequencing of this mitochondrial DNA hybrid revealed a mosaic structure with many specific mutations. The origin of this hybrid sequence is discussed. 574 563 0,938 3,43 Q1 Q1 SCIE